Forensic Accounting Techniques and Fraud Prevention in Quoted Food and Beverages Companies in Nigeria - Aina, Grace O.; Oyetunji, Oluwayomi T.; Lawal, Babatunde A.; Dada, Gbemisola A. (NIU Journal of Humanities; Vol. 10 Núm. 1 (2025): NIU Journal of Humanities, Vol. 10 No. 1, March 2025, 2025)
Studies have shown that, the manufacturing sector in Nigeria has experienced difficulties over the years due to fraudulent activities under different conditions and that led to a decline and fluctuations in the financial performance. This study therefore investigates forensic accounting techniques and fraud prevention in quoted food and beverages companies in Nigeria. The study adopted research survey design. The population of study comprised 20 food and beverage manufacturing firms listed on the Nigerian Exchange Group (NGX) as at December 31 st , 2023. Fourteen (14) food and beverage manufacturing firms were selected using purposive sampling technique. Descriptive and inferential statistics was used to analyse data collected. The results revealed that forensic accounting techniques had a significant effect and positive on fraud prevention (whistle blowing practices (Adj. R 2 = 0.506, F 64.555 = 0.000, P < 0.05) and continuous monitoring (Adj. R 2 = 0.605, F 65.556 = 0.000, P < 0.05) of listed food and beverage manufacturing firms in Nigeria. The study concludes that the application of forensic accounting techniques has effect on financial integrity and fraud prevention; and strategies such as computer aided auditing techniques and trend analysis techniques improve organization's capacity to stop fraudulent activities. The study recommends that management should integrate forensic accounting techniques in the company to prevent fraud and enhance overall financial integrity. Keywords: Assets usage, continuous monitoring, data mining, forensic accounting, fraud prevention, manufacturing, financial performance, trend analysis, fraudulent activities, and financial integrity